Mapping MMS Observations of Solitary Waves in Earth's Magnetic Field. Issue 12 (6th December 2021) - Hansel, P. J.; Wilder, F. D.; Malaspina, D. M.; Ergun, R. E.; Ahmadi, N.; Holmes, J. C.; Goodrich, K. A.; Fuselier, S.; Giles, B.; Russell, C. T.; Torbert, R.; Strangeway, R.; et al.
Abstract: Electrostatic solitary waves (ESWs) are a type of nonlinear time‐domain plasma structure (TDS) generally defined by bipolar electric fields and propagation parallel to the local magnetic field. Formation mechanisms for TDSs in the magnetosphere have been studied extensively and are associated with plasma boundary layers and the braking of bursty bulk flows (BBFs). However, the rapid timescales over which these TDSs occur (<2 ms) make them infeasible to count by eye over large time periods. Furthermore, high‐cadence data are not always available. The Solitary Wave Detector (SWD) on NASA's Magnetospheric Multiscale (MMS) mission quantifies the occurrence and amplitude of TDS throughout the constellation's orbit; analysis of burst (65 kS/s) parallel electric field data indicates that the SWD captures approximately 60% of all bipolar TDS encountered in the tail region, enabling large‐scale examination of their occurrence. Maps of TDS occurrence rates during several years of the MMS mission were generated from SWD data, showing enhanced TDS density in the tail region between 6 and 9 Re; enhance occurrence in or near shocks; and an unexpected enhancement in the dawn side of the tail and in the radiation belt. Key Points: The MMS Solitary Wave Detector records time‐domain structures in Earth's magnetosphere SWD maps highlight regions like the Van Allen belts and the bursty bulk flow braking region The SWD shows intriguing nonlinear activity in the shocks, magnetotail, flank, and dawn‐side outer radiation belt